Roles of cytotoxic lymphocytes and MIC/LILR families in pathophysiology of Takayasu arteritis - Hajime Yoshifuji; Chikashi Terao (BMC, 2020)
Abstract Takayasu arteritis (TAK) affects the aorta and its primary branches, mainly in young women. In its advanced stages, it can cause severe complications, such as cerebral infarction, impaired vision, and valvular heart diseases. In the aortic tissue of TAK, there is increased infiltration of cytotoxic lymphocytes, such as natural killer (NK) cells and CD8+T cells, and enhanced expression of accessory molecules, such as major histocompatibility complex (MHC) and MHC class I chain-related gene (MIC) family. Genome-wide association studies on TAK have identified susceptibility genes, such as IL-12p40, MICA, MICB, leukocyte immunoglobulin-like receptor A3 (LILRA3), and LILRB3. Other studies have also shown their involvement in the pathophysiology of TAK. In addition, we reported the importance of NK cells by enhancer enrichment analysis. These results suggest that the gene polymorphisms that potentially upregulate the expression of cytokines and accessory molecules, which contribute to the activation of cytotoxic lymphocytes, are associated with the development of TAK. Based on these results, new molecular targeted therapies look promising.